Detection of CTX-M gene in extended spectrum beta lactamase (ESBL) producing Escherichia coli and Klebsiella species of different hospitals. - Rahman, Nawshad Muhammad Wahidur; Lutfor, Afzalunnessa Binte; Jhora, Sanya Tahmina; Yasmin, Mahmuda; Haq, Jalaluddin Ashraful (Bangladesh Journal of Medical Microbiology, 2012)
A total of 200, non-duplicate ESBL producing strains (171 Escherichia coli and 29 Klebsiella spp.) from three tertiary care hospitals were detected using screening test & double disc synergy test. All isolates were screened for the detection of CTX-M type Extended spectrum Beta-lactamase (ESBL) using PCR. Among them 133 (66.5%) were positive for CTX-M type ESBLs which include 114 (66.66%) E.coli and 19 (65.51%) Klebsiella spp. This is the first report of identifying CTX-M gene in ESBL producing Escherichia coli and Klebsiella species of different hospitals. DOI: http://dx.doi.org/10.3329/bjmm.v4i2.10829